Scientific knowledge about infections by the new coronavirus in older adults: a scoping review - Darlene Mara dos Santos Tavares; Nayara Gomes Nunes Oliveira; Marina Aleixo Diniz-Rezende; Graziele Ribeiro Bitencourt; Marcos Barragan da Silva; Alisson Fernandes Bolina
ABSTRACT Objective: to map the scientific knowledge about COVID-19 in older adults. Method: this is a scoping review literature review. A search was performed in the PubMed, CINAHL, Web of Science and LILACS databases. Original articles that answered the guiding question were included: what scientific knowledge is available in the world about COVID-19 in older adults? Results: thirty-one articles were included, most of them carried out in China (n=23) and with a retrospective design (n=13) and case studies/case series (n=13). Based on the findings, six thematic categories emerged: clinical signs and symptoms (n=12), other information (n=9), adverse outcomes/complications resulting from COVID-19 (n=8), age relationship and greater severity of COVID-19 (n=8), variables related to death by COVID-19 (n=8), and diagnostic findings (n=8). Conclusion: the findings reinforce older adults' greater vulnerability to the worsening of COVID-19, as well as to complications resulting from the disease, including the greater occurrence of death.